2018
DOI: 10.15761/pmrr.1000191
|View full text |Cite
|
Sign up to set email alerts
|

Creating a standardized, quantitative training protocol for upper limb bypass prostheses

Abstract: We aim to present a standard protocol for training able-bodied individuals to use a body-powered bypass prosthesis and assess training length and impact of prepositioning. The protocol design and subsequent analysis aims to facilitate controlled and efficient implementation of the able-bodied bypass user in the research setting. Six volunteers completed ten two-hour sessions with a body-powered bypass prosthesis. Each session included standardized training tasks: object manipulation, free training, and activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…However, no study on the BBT has shown the average age prosthetic users of BBT for. Previous studies have used an average of 25-30 blocks when assessing prosthetic control skills with the BBT [31,32]. In this study, the average P2 score for each group was 25-28 blocks with and without intervention, which was similar to the average score in previous papers.…”
Section: Vr Effect Depending On Task Difficultysupporting
confidence: 79%
“…However, no study on the BBT has shown the average age prosthetic users of BBT for. Previous studies have used an average of 25-30 blocks when assessing prosthetic control skills with the BBT [31,32]. In this study, the average P2 score for each group was 25-28 blocks with and without intervention, which was similar to the average score in previous papers.…”
Section: Vr Effect Depending On Task Difficultysupporting
confidence: 79%
“…Participants completed the training protocol outlined by Bloomer et al. 24 The protocol required participants to complete 10 sessions with a duration of 2 hours each sessions to balance the amount of time typically provided to train bypass prosthesis users on devices (up to several weeks) 7 , 19 and the time commitment of the study participants. Training activities focused on basic object manipulation tasks and activities of daily living while emphasizing thoughtful planning before attempting a task, such as prepositioning of the terminal device specifically for the body-powered device or determining the appropriate grip to use for the DEKA arm.…”
Section: Methodsmentioning
confidence: 99%
“…However, there is no study showing the average age of BBT for prosthetic users. Previous studies have reported an average of 25-30 blocks in assessing prosthetic control skills using BBT [22,23]. In this study, the average score of each group in Post2 is 25-28 blocks.…”
Section: Vr Effect Depending On Task Difficultymentioning
confidence: 81%